Effects of Simulation Practicum Using Flipped Learning for Korean Nursing Students - Gu, Minkyung (Int J Environ Res Public Health, 2020)
This study aimed to examine the effects of simulation practicum using flipped learning on nursing competency, core basic nursing skill (subcutaneous injection) performance, self-efficacy, and learning satisfaction of Korean nursing students. This study used a quasi-experimental pretest-posttest control group design. The samples used were from 101 nursing students (Intervention 1: n = 34; Intervention 2: n = 34; Control: n = 33) over 20 years old in G provinces, Korea. For the experimental interventions, participants in the intervention group 1 were applied by simulation practicum using flipped learning, and those in intervention group 2 were applied by simulation practicum. Participants in the control group were applied by lecture-based practicum using a model. The measures were the study participants’ general characteristics survey, the nursing competency scale, the core basic nursing skill (subcutaneous injection) performance scale, the self-efficacy scale, and the learning satisfaction scale. There were statistically significant differences in nursing competency, core basic nursing skill (subcutaneous injection) performance, self-efficacy, and the learning satisfaction among the three groups. It was seen in this study that simulation practicum using flipped learning was the most effective teaching and learning method for the nursing practicum of Korean nursing students. The simulation practicum using flipped learning can be useful in providing nursing practicum to nursing students.